(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
The issue of limited learning media and students’ difficulties in understanding the material prompted the author to conduct this research. Based on an analysis of the textbooks used, the material presented is general in nature and not connected to local wisdom relevant to students’ surroundings. This study aims to: (1) design an Animaker-based instructional video integrating local wisdom; (2) assess its feasibility; and (3) evaluate its practicality. The research method used is Research and Development (R&D) with the Alessi and Trollip model.The results indicate that the developed instructional video is highly feasible and practical for use. Validation results showed the following scores: material expert 93.8%, media expert 91.5%, and language expert 98.4%—all rated as “Highly Feasible.” Practicality tests by classroom teachers yielded scores of 100% (Grade IV-A) and 94% (Grade IV-B), both categorized as “Highly Practical.” The student practicality test yielded a score of 88.8%, also rated as “Highly Practical.” Therefore, the Animaker-based instructional video integrating local wisdom is suitable for use in learning, particularly in introducing the local wisdom of Nagan Raya at MIN 1 Nagan Raya. Keywords: Animated Videos, Animaker Apps, Local Wisdom.